2020
DOI: 10.1097/jom.0000000000001932
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Disorders Resulting From Exposure to Low Concentrations of Ammonia

Abstract: Objective: This study aimed to investigate respiratory disorders associated with exposure to low concentrations of ammonia. Method: This cohort study was conducted on 122 industrial workers. Data gathering were based on the officially registered data, the NMAM 6016 and the American Thoracic Society and European Respiratory Society protocols. Results: The prevalence rate of respiratory disorders significantly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…A major strength is the long-term measurement of ve pollutants with standardized and high quality sampling techniques and instruments resulting in reliable levels of airborne concentrations in the vicinity of the petrochemical plant. (57,74) and respiratory symptoms, the current study focused on these pollutants rather than other petrochemical airborne chemicals such as VOCs. Although air concentrations of gaseous pollutions were measured in a reliable way, we did not have individual exposure data and had to assume a constant level of exposure among all workers in the petrochemical plant.…”
Section: Discussionmentioning
confidence: 99%
“…A major strength is the long-term measurement of ve pollutants with standardized and high quality sampling techniques and instruments resulting in reliable levels of airborne concentrations in the vicinity of the petrochemical plant. (57,74) and respiratory symptoms, the current study focused on these pollutants rather than other petrochemical airborne chemicals such as VOCs. Although air concentrations of gaseous pollutions were measured in a reliable way, we did not have individual exposure data and had to assume a constant level of exposure among all workers in the petrochemical plant.…”
Section: Discussionmentioning
confidence: 99%
“…This study also found a significant decrease in FVC (p = 0,01) and FEV 1 (p=0,05) during the work shift among workers in urea factory. Study by Mahdinia et al 12 showed that exposure and the amount of exposure to ammonia had a significant relationship with respiratory disorders and respiratory function ( P < 0,05).…”
Section: Strength Of Associationmentioning
confidence: 97%
“…Mahdinia M et al 12 followed the subjects for five years and obtained exposure and the amount of exposure to ammonia had a significant relationship with respiratory disorders and respiratory function ( P < 0,05). Meanwhile, the other four articles did not follow their subjects for a certain period of time.…”
Section: Specificitymentioning
confidence: 99%
See 2 more Smart Citations